Model training of future specialists in human health to strengthen the use of health technologies - Mikheenko, O. I.; Kotelevsky, V. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : develop a model of scientific and methodological training of future specialists in human health to strengthen the use of health technologies. Material : processed more than 100 literary sources. Results : analyzed the methodological, organizational and educational and training aspects of the training of future specialists in human health. On the basis of scientific modeling, the basic structural components of the model of professional training of future specialists, are characterized by their nature and relationship. Theoretical basis to ensure a high level of training future specialist is an integral concept of professionalization based on the theoretical and methodological basis of its essence. Conclusions : it is proved that the effectiveness of training future specialist determined holistic concept of professionalization and relevant scientific and methodological support of the educational process.